Holistic and reductionist thinker: a comparison study based on individuals' skillset and personality types. (28th December 2020) - Nagahi, Morteza; Jaradat, Raed; Amrani, Safae El; Hamilton, Michael; Goerger, Simon R.
As organisations operate in turbulent and complex environments, it has become a necessity to assess the systems thinking (ST) skills, personality types (PTs), and demographics of practitioners. In this study, we investigated the relationship between practitioners' ST profile, their PTs profiles and demographic characteristics in the domain of complex system problems. The objective of this study is to address the current gap in the literature - lack of studies dedicated to predicting practitioners' ST profile based on their PTs and demographics characteristics. A total of 258 practitioners with different demographics and PTs provided the data. The results show that (1) practitioners can be classified based on their ST skills scores into two clusters: holistic and reductionist (that is, ST profile), (2) each cluster has different PTs profiles and demographic characteristics, and (3) practitioner's ST profile can be predicted, with good accuracy, based on their PTs profile and demographic characteristics.